Longitudinal patterns in fear of cancer progression in patients with rare, advanced cancers undergoing comprehensive tumour genomic profiling. Issue 11 (14th July 2021) - Butow, Phyllis; Müller, Fabiola; Napier, Christine E.; Bartley, Nicci; Ballinger, Mandy L.; Biesecker, Barbara; Juraskova, Ilona; Meiser, Bettina; Schlub, Timothy E.; Thomas, David M.; Goldstein, David; Best, Megan C.; et al.
Abstract: Introduction: Fear of cancer progression (FCP) impacts quality of life and is a prevalent unmet need in patients diagnosed with advanced cancer, particularly as treatment options are reduced. We aimed to identify longitudinal patterns in FCP over 6 months in patients with advanced cancer receiving comprehensive tumour genomic profiling (CTGP) results, and their correlates. Methods: Patients with pathologically confirmed metastatic disease (∼70% rare cancers) receiving or post their last line of standard therapy completed questionnaires at T0 (prior to CTGP), T1 (immediately post CTGP results) and T2 (2 months later). Results: High stable ( N  = 52; 7.3%) and low/moderate stable ( N  = 56; 7.8%) FCP patterns over time typified the largest participant groups ( N  = 721). Those with an immediately actionable variant versus a non‐actionable variant ( p  = 0.045), with higher FCP ( p  < 0.001), and lower Functional Assessment of Chronic Illness Therapy—Spiritual Well‐being (FACIT‐Sp) scores ( p  = 0.006) at T0, had higher FCP at T1. Those with higher FCP at T0 ( p  < 0.001) and at T1 ( p  < 0.001), lower FACIT‐Sp scores at T1 ( p  = 0.001), lower education ( p  = 0.031) and female gender ( p  = 0.027) had higher FCP at T2. Discussion: Routine screening for psychological/spiritual characteristics in those about to undergo CTGP may help to identify patients who may benefit from closer monitoring and provision of psychosocial support. Future studies should explore interventions to best address FCP in this vulnerable group, as interventions assessed to date have almost all addressed patients with curative cancers or newly diagnosed advanced disease.